Marine Omega3 wound matrix for the treatment of complicated wounds - Trinh, T. T.; Dünschede, F.; Vahl, C.-F.; Dorweiler, B. (Phlebologie, 2016)
Introduction Complicated wounds in the lower extremity can arise as a consequence of insufficient soft-tissue coverage after amputations in diabetic patients. The Kerecis® Omega3 wound matrix is a decellularized skin matrix derived from codfish and represents an alternative treatment option to achieve wound healing.Methods 5 patients with diabetes mellitus and complicated wounds in the lower limb with exposed bony segments were treated with the Omega3 wound matrix between November 2014 and November 2015. Following initial debridement in the operating room, the wound matrix was applied and covered with a silicone mesh. In the further course, wound treatment was conducted on outpatient setting.Results In total, 7 wounds were treated with localization at the level of the thigh (n=2) and the forefoot (n=5). For the wounds at the thigh, it took 26 weeks to achieve wound closure, whereas the wounds at the level of the forefoot showed healing times between 13 and 41 weeks. In all patients, a reduction of analgetics intake was noted when the treatment with the Omega3 wound matrix was initiated.Conclusion The Kerecis® Omega3 wound matrix represents a viable treatment option in complicated wounds in the lower limb of diabetic patients to circumvent an otherwise necessary proximalization of amputation level. Further studies comparing the Omega3 wound matrix with appropriate control groups of standard therapies for soft-tissue conditioning/coverage like negative pressure therapy, biosurgery and other acellular dermal matrices are warranted.
Keywords: Diabetic ulcer; wound healing; wound matrix; amputation